Technology, entrepreneurship, and inequality - Alfonso Gambardella; David Ulph (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
This paper links the rise of new industries populated by skill-intensive companies, and the divergence in labour incomes between skills. Our model explains inequality by the fact that as the skilled workers move towards new Silicon-Valley type firms, the reduced complementarity between skilled and unskilled workers in the traditional manufacturing sectors lessens the productivity of the latter. In addition, knowledge externalities in the modern sector produce two equilibria in which either the modern sector dominates (and inequality between skills is high), or manufacturing dominates (inequality is low). We provide suggestive evidence consistent with our model.
Keywords: J32; L22; 330; technology; entrepreneurship; wage inequality; Lohnstruktur; Qualifikation; Technischer Fortschritt; Unternehmensgründung; Theorie